Studi Preliminer Pemanfaatan Lumpur Vulkanik Sidoarjo Sebagai Adsorben Zat Warna Napthol di Air Limbah Batik - Septi Fatimatus Zahro; Sandyanto Adityosulindro (Universitas Riau, 2024)
The Sidoarjo Volcanic Mudflow has been one of Indonesia's ongoing national catastrophes since 2006. Numerous studies have been conducted to examine the potential applications of this abundant material due to its massive quantity. In this work, Sidoarjo Volcanic Mud was utilized as a dye-removing adsorbent in batik wastewater. To increase the effectiveness of Sidoarjo Volcanic Mud as an adsorbent, physical and chemical activation techniques were employed, and the results were compared to a control without activation. The sample was heated at 550 °C for three hours to be physically activated. The sample was chemically activated by applying 5N H2SO4 solution for 2.5 hours. In a batch system with an orbital shaker, adsorption tests were conducted for the color removal of pure and pre-treated batik wastewater. Using UV-Vis spectrophotometry, the decolorization of batik wastewater was monitored during the reaction. Due to the high concentration of apparent color in the sample, the effect of the adsorbent activation method was insignificant in pure batik wastewater. In contrast, the effect of the adsorbent activation method was evident in pre-treated batik wastewater, where up to 50% decolorization of the true color was achieved with chemically activated, 18.75% with no activation, and 23.30% with physical activation.